The Sacramental Ontology of the Church: Toward a Renewal Ecclesiology - Davis, Melissa (Pneuma, 2021)
Abstract This article seeks to construct a renewalist ecclesiology foundations on the idea that the church is an ontological reality with the epistemological purpose of traditioning its members. To accomplish this, I construct, in conversation with Simon Chan and Simon Oliver, a sacramental ontology of the invisible church from the Garden of Eden via the incarnation. Then, interacting with the work of Chan and James K.A. Smith, I explore the role of the visible church to tradition its members. Finally, I offer a framework for an ecclesial traditioning praxis. This praxis is founded in prayer, shaped by the narrative of Scripture, and utilizes both the weekly service and ongoing discipleship training.